Prediction of quality of life among the elderly based on level of depression and spirituality - Salsabila, Nadia Nandina; Ariani, Tutu April; Aini, Nur; Marta, Ollyvia Freeska Dwi; Mashfufa, Erma Wahyu (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2024)
Introduction: Quality of life (QoL) in the elderly is shaped by physical, psychological, and spiritual factors. Depression commonly affects older adults and is linked to poorer QoL, while spirituality can offer resilience. However, the combined impact of depression and spirituality on elderly QoL is seldom explored. Purpose: This study aims to investigate the relationship between depression, spirituality, and QoL among elderly individuals in nursing homes, examining how these factors influence their physical, social, and mental well-being. Methods: This study used a cross-sectional study design conducted on nursing home residents. The study population was elderly living in nursing homes, with a sample size of 73 people selected by convenience sampling and calculated using G*power software. Quality of life (QoL) was measured using the SF-36 questionnaire, spirituality was measured using the Spiritual Well-Being Scale (SWBS), and depression was measured using the Beck Depression Inventory-II (BDI-II). Data analysis was performed using multiple logistic regression to analyze the relationship between the study variables. Results: Mean scores for physical and mental components of QoL were 50.06 (Â±6.80) and 50.22 (Â±8.73), respectively. Spirituality was positively associated with QoL, especially in social (AOR 1.15) and mental health (AOR 1.06) dimensions (p < 0.05). Depression was negatively related to vitality (AOR 1.11) and mental health (AOR 1.09), showing that greater spirituality aligns with higher QoL, while depression correlates with poorer QoL. Conclusion: Spiritual well-being and depression significantly impact elderly QoL, particularly in social, vitality, and mental health aspects.